2019
DOI: 10.3390/nu11061367
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diets with Varying Essential/Nonessential Amino Acid Ratios on Mouse Lifespan

Abstract: An adequate intake of essential (EAA) and non-essential amino acids (NEAA) is crucial to preserve cell integrity and whole-body metabolism. EAA introduced with diet may be insufficient to meet the organismal needs, especially under increased physiological requirements or in pathological conditions, and may condition lifespan. We therefore examined the effects of iso-caloric and providing the same nitrogenous content diets, any diet containing different stoichiometric blends of EAA/NEAA, on mouse lifespan. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…The sago grub met the FAO/WHO (1973) requirements of 40% essential amino acids and a 0.60 ratio between essential to non-essential amino acids. In a study on mice by Romano et al (2019), it was concluded that the ratio among EAA and NEAA is the most probable factor responsible for the healthpromoting effects of proteins, and that the higher the ratio (closer to 1 or even greater than 1 if supplemented with additional EAA) in the diet, the more efficient it is to increase the lifespan of people suffering from malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The sago grub met the FAO/WHO (1973) requirements of 40% essential amino acids and a 0.60 ratio between essential to non-essential amino acids. In a study on mice by Romano et al (2019), it was concluded that the ratio among EAA and NEAA is the most probable factor responsible for the healthpromoting effects of proteins, and that the higher the ratio (closer to 1 or even greater than 1 if supplemented with additional EAA) in the diet, the more efficient it is to increase the lifespan of people suffering from malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…This value is an indication that the larva is a good source of amino acid. In a study on mice by Romano et al [12], it was concluded that the ratio among EAA and NEAA is the most probable factor responsible for the health-promoting effects of proteins, and that the higher the ratio (closer to 1 or even greater than 1 if supplemented with additional EAA) in the diet, the more efficient it is to increase the lifespan of people suffering from malnutrition.…”
Section: Resultsmentioning
confidence: 99%
“…While certain components of aliments positively contribute to protein synthesis [41], autophagy [40], mitochondrial biogenesis, and also reduce renal [37], cardiac and muscular fibrosis and increased life span [26], other components (non essential amino acids: NEAA) acts in an opposite manner, resulting in reduced lifespan [6] not just a question of adequate intake of sufficient amounts of EAA, but of intake relative to NEAA introduction, which, if in excess, blunts EAA effects. Also, not all formulations providing EAA exert the same effects.…”
Section: Regulation Of Protein Syntheses: a Provocative Functional VImentioning
confidence: 99%
“…Despite eating up to 60% more food, with quantity to compensate for the lack of quality of AAs, rapid wasting leading to a mortal cachexia occurred in animals fed 30% EAA and 70% NEAA, an amount just 15% less EAA than those provided by the vast majority of alimentary proteins. Animals that had the choice among different pellets, always largely selected the most NEAA-rich, and also the most deadly content [6].…”
Section: Regulation Of Protein Syntheses: a Provocative Functional VImentioning
confidence: 99%
See 1 more Smart Citation